PENGEMBANGAN GAME EDUKATIF BERORIENTASI KEMAMPUAN BERPIKIR LOGIS KELAS 2 SEKOLAH DASAR - Ashari, Rahmat; Syarif, Ahmad; Budiono, Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of learning in the digital era requires instructional media that are not only engaging but also capable of enhancing students’ logical thinking skills at the elementary school level. However, classroom observations in Grade II revealed that students’ logical thinking abilities remain limited, particularly in understanding and using simple vocabulary, as well as teachers’ constraints in utilizing appropriate digital learning media. This study aimed to develop an educational game oriented toward logical thinking skills for Grade II elementary school students and to determine the validity and practicality of the developed product. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The developed product is a web-based educational game created using the Interacty platform, featuring Indonesian language vocabulary related to the school environment and game activities designed based on logical thinking indicators. Data were collected through expert validation sheets (content, language, and media experts) and response questionnaires from teachers and students. The results indicate that the developed educational game achieved a very high level of validity and was categorized as practical for classroom use. Therefore, the educational game is feasible to be implemented as a learning medium to support the development of logical thinking skills among Grade II elementary school students.